Improving Cash Flow Management - Abbasov, S. (Економічний вісник Донбасу, 2021)
The article discusses various scientific and theoretical views of famous economists on the essence, purpose and objectives of cash flow as an object of financial management and makes appropriate conclusions. Cash flow has a unique property of financial liquidity and fully implements the economic functions that relate to it. Cash flow management is a financial tool that allows you to achieve high final results of the financial and economic activities of the company, that is, maximize profits. The principles, methods and a comprehensive analysis of cash flow management are considered. The stages of the cash flow management process and their information support are described in detail. The principles and stages of creating an organizational and functional cash flow management mechanism were considered and emphasized that the formation of an excellent cash flow management mechanism will allow the company to attract additional investments to carry out its current activities and enter foreign markets, including the stock market. Issues of disclosing shadow cash flows in financial management and determining its role in increasing the value of the company and the risks associated with macroeconomic regulation have been studied in detail. There are reasonable suggestions and recommendations for improving the cash flow management mechanism. У статті розглядаються різні науково-теоретичні погляди відомих економістів на сутність, призначення та завдання грошового потоку як об’єкта фінансового менеджменту та зроблено відповідні висновки. Грошовий потік має унікальну властивість фінансової ліквідності і повною мірою реалізує економічні функції. Управління грошовими потоками є фінансовим інструментом, що дозволяє досягти високих кінцевих результатів фінансово-господарської діяльності підприємства, тобто максимізувати прибуток. Розглянуто принципи, методи та комплексний аналіз управління грошовими потоками. Детально описано етапи процесу управління грошовими потоками та їх інформаційне забезпечення. Розглянуто принципи та етапи створення організаційно-функціонального механізму управління грошовими потоками та підкреслено, що формування відповідного механізму управління грошовими потоками дозволить підприємству залучити додаткові інвестиції для здійснення поточної діяльності та виходу на зовнішні ринки, у тому числі на фондові ринки. Детально досліджено питання розкриття тіньових грошових потоків у фінансовому менеджменті та визначення його ролі у підвищенні вартості компанії та ризиків, які пов’язані з макроекономічним регулюванням. Є обґрунтовані пропозиції та рекомендації щодо вдосконалення механізму управління грошовими потоками. В статье рассматриваются разные научно-теоретические взгляды известных экономистов на суть, назначение и задачи денежного потока как объекта финансового менеджмента и сделаны соответствующие выводы. Денежный поток обладает уникальным свойством финансовой ликвидности и в полной мере реализует экономические функции. Управление денежными потоками является финансовым инструментом, позволяющим достичь высоких конечных результатов финансово-хозяйственной деятельности предприятия, то есть максимизировать прибыль. Рассмотрены принципы, методы и комплексный анализ управления денежными потоками. Подробно описаны этапы процесса управления денежными потоками и их информационное обеспечение. Рассмотрены принципы и этапы создания организационно-функционального механизма управления денежными потоками и подчеркнуто, что формирование соответствующего механизма управления денежными потоками позволит привлечь предприятию дополнительные инвестиции для осуществления текущей деятельности и выхода на внешние рынки, в том числе на фондовые рынки. Подробно исследованы вопросы раскрытия теневых денежных потоков в финансовом менеджменте и определения его роли в повышении стоимости компании и рисков, связанных с макроэкономическим регулированием. Обоснованы предложения и рекомендации по совершенствованию механизма управления денежными потоками.